Evaluation of the on-line commercial service quality based on association rules - Szyda, Monika; Czarnowski, Ireneusz (Ocena jakości usług handlowych on-line na podstawie analizy reguł asocjacyjnych, 2017)
The existing approaches to the evaluation of on-line commercial services quality include various quality indicators. The application of multiple attributes for quality evaluation enables and involves specialized analysis techniques to carry it out. This article proposes to utilize association rules in the quality evaluation of the on-line services. The analysis carried out of the discovered association rules has provided interesting dependencies and relationships on the individual characteristics of the on-line commercial service. On the basis of such on analysis, conclusions can be made regarding the general quality of the on-line commercial services. The discovered dependencies and connections can be used in shaping online commercial service quality. Conclusions from the analysis of the association rules can therefore be used to improve the on-line commercial service quality comprehensively which can lead to the higher satisfaction of e-customers
Informatyka Ekonomiczna = Business Informatics, 2017, Nr 1 (43), s. 66-85
Keywords: e-commerce; e-quality evaluation; e-customer satisfaction; association rules; data mining; jakość usług handlowych on-line; satysfakcja e-klienta; reguły asocjacyjne